The Effect of E-Service Quality and Customer Relationship Management of User Customer Loyalty Gopay on Gojek App - Satrio Bimo Syahputro; Rahmi Rahmi; Vandi Verdiansyah; Muhammad Nur Rohman; Uci Sumiati (University of Science and Computer Technology, 2023)
The purpose of this study is to determine the effect of E-Service Quality and Customer Relationship Management on Customer Loyalty of Gopay Users on the Gojek App. The type of research in this study is quantitative with the population in this study being Gopay users in Tanjungpinang City. In the technique for sampling using the Slovin formula, with a total sample of 87 respondents. The results of this study are known that E-Service Quality and Customer Relationship Management simultaneously affect the variables of Customer Loyalty. The amount of contribution of E-Service Quality and Customer Relationship Management to the User Loyalty variable is 71.9%. And the remaining 20.7% is the influence of other variables that are not included in the regression model of this study.